2021
DOI: 10.3390/medicina57030254
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Seroprevalence of Helicobacter pylori among the Lithuanian Medical Students over the Last 25 Years and Its Relation to Dyspeptic Symptoms

Abstract: Background and Objectives: The prevalence of Helicobacter pylori infection is decreasing in the Western world, while remaining high in developing countries. There is limited up-to-date information about the prevalence of H. pylori in Central and Eastern Europe. The aim of our study was to assess the seroprevalence of H. pylori and its trend over the past 25 years among students of the Lithuanian University of Health Sciences (LUHS) and to assess its relation to dyspeptic symptoms. Materials and Methods: In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
5
0
3
Order By: Relevance
“…Furthermore, the prevalence may vary based on ethnic groups: Indigenous people in most countries are more susceptible to being infected[ 2 ]; a study in the United Arab Emirates showed a higher H. pylori prevalence among Africans than in Asian and Arabic populations, and, despite living in similar conditions to other ethnic groups, Malays were notably less affected by H. pylori infection than other people in that country[ 18 - 20 ]. In another study, Jonaityte et al [ 21 ] found a decline in the seroprevalence of H. pylori among medical students from Lithuania, with seroprevalences of 51.7, 30.4, 26.3, and 14.2% in 1995, 2012, 2016, and 2020, respectively. Besides, Africa, Western Asia, and South America are the regions with the highest incidence of H. pylori , while Oceania, North America, and Western Europe have lower prevalences of the bacterium[ 2 ].…”
Section: Prevalencementioning
confidence: 99%
“…Furthermore, the prevalence may vary based on ethnic groups: Indigenous people in most countries are more susceptible to being infected[ 2 ]; a study in the United Arab Emirates showed a higher H. pylori prevalence among Africans than in Asian and Arabic populations, and, despite living in similar conditions to other ethnic groups, Malays were notably less affected by H. pylori infection than other people in that country[ 18 - 20 ]. In another study, Jonaityte et al [ 21 ] found a decline in the seroprevalence of H. pylori among medical students from Lithuania, with seroprevalences of 51.7, 30.4, 26.3, and 14.2% in 1995, 2012, 2016, and 2020, respectively. Besides, Africa, Western Asia, and South America are the regions with the highest incidence of H. pylori , while Oceania, North America, and Western Europe have lower prevalences of the bacterium[ 2 ].…”
Section: Prevalencementioning
confidence: 99%
“…Według autorów odpowiedzialna jest za to poprawa warunków sanitarnych, mieszkaniowych i ekonomicznych. Badania przeprowadzone w latach 1995-2020 przez Jonaityte et al (9), wykazały że w 1995 roku aż 51,7% litewskich studentów miało swoiste przeciwciała dla H. pylori. W kolejnych latach zauważono istotny spadek częstości występowania tych immunoglobulin: w 2012 roku odsetek ten wynosił 30,4%, w 2016 roku 26,3%, by ostatecznie spaść do poziomu 14,2% w 2020 roku.…”
Section: Discussionunclassified
“…Poziom przeciwciał dla H. pylori u 240 losowo wybranych dzieci w wieku od 6 miesięcy do 17 lat zamieszkałych w Łodzi zbadali w 1996 roku Czkwianianc et al (19). Najrzadziej swoiste przeciwciała wykrywano u najmłodszych dzieci, <5 roku życia (15-16,6%), nieco częściej u dzieci w wieku 6-10 lat (28,3%), a najczęściej, bo aż w 41,6% przypad-between 1995 and 2020 by Jonaityte et al (9) in 1995 showed that as many as 51.7% of Lithuanian students had specific antibodies to H. pylori. In the following years, a significant decrease in the frequency of these immunoglobulins was noticed: in 2012 this percentage was 30.4%, in 2016 26.3%, and finally dropped to 14.2% in 2020.…”
Section: Discussionunclassified
“…However, it is most likely that these patients did not undergo confirmatory tests as they were not sufficiently motivated to do it by the responsible healthcare professional or by themselves. As the prevalence of H. pylori in Lithuania is still quite high [ 14 , 15 , 16 , 17 ], a much higher rate of treatment evaluation could result in better treatment outcomes and more rapid decrease in the prevalence of this infection. We would also like to state that the only way to improve H. pylori cure rates is to better know what the current situation of H. pylori diagnostics and treatment in Lithuania looks like, and for doing that, confirmation of H. pylori eradication as a general rule is necessarily needed.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of epidemiological H. pylori studies in Lithuania—already published articles have shown the prevalence of H. pylori ranging from 36% in children [ 14 ] up to 70% in adults [ 15 , 16 ]. A most recent study has shown that over the last 25 years (1995–2020) the prevalence of H. pylori has decreased significantly from 52% to 14% among the students of Lithuanian University of Health Sciences [ 17 ]. Moreover, the reinfection rate of H. pylori in Lithuania is still relatively high [ 18 ].…”
Section: Introductionmentioning
confidence: 99%